CO2 adsorption material based on corrugated plate white blank as well as preparation method and application of CO2 adsorption material

By using corrugated plate white embryos as a carrier, combined with modifier and K2CO3 treatment, the problems of K2CO3-based CO2 adsorbent materials in circulation durability and molding difficulty are solved, and efficient CO2 capture and reduce operating costs are achieved.

CN119897078APending Publication Date: 2025-04-29XIAN THERMAL POWER RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510054760.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing K2CO3-based CO2 adsorbent materials have limited their industrial applications due to poor circulation durability, difficult forming and high operational difficulties.

Method used

Modular CO2 adsorption material was prepared by using commercial corrugated plate white embryos as carrier, and by adding modular solution and K2CO3 solution for impregnation, drying and calcination.

Benefits of technology

The CO2 capture capacity of CO2 adsorbent material is increased to 1.0~1.9 mmol/g, which reduces the operating cost of adsorbent replacement and has good industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897078A_ABST
    Figure CN119897078A_ABST
Patent Text Reader

Abstract

The invention discloses a CO2 adsorption material based on a corrugated plate white blank as well as a preparation method and application of the CO2 adsorption material. Based on a commercial corrugated plate white blank carrier, on the basis of giving full play to the characteristics of three-state pores (micropores, mesopores and macropores) of the carrier, after the microscopic specific surface area of the carrier is further increased through PVP and a urea pore-forming agent, loading of an adsorption active substance K2CO3 is carried out, the loading amount of K2CO3 is increased, meanwhile, the reaction contact surface is also increased, and the adsorption efficiency is obviously improved; and meanwhile, modular preparation of the adsorption material can be realized based on carrier characteristics, and a foundation is laid for later industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of atmospheric environmental protection, and specifically relates to a CO2 adsorption material based on a corrugated plate blank, and a preparation method and application thereof. Background Art

[0002] CCUS (Carbon Capture, Utilization and Storage) technology has received widespread attention. At present, the liquid phase absorption technology using organic amine solution as the absorption material has become relatively mature and complete, and the relevant industrial demonstration has been built and put into operation. The liquid phase absorption method has efficient carbon capture capacity, but it also faces the limitations of high energy consumption, high cost, and easy corrosion of equipment. Therefore, solid phase adsorption has gradually attracted people's attention in recent years. The current mainstream solid phase adsorption materials include molecular sieves, MOF, MgO, K2CO3, solid amines, etc. Compared with the liquid phase absorption method, the solid phase adsorption method has strong adaptability, no corrosion, no secondary pollution, and great potential for commercial application.

[0003] K2CO3 has a good adsorption effect on CO2 in the low temperature range. Based on the following chemical reaction, K2CO3 can adsorb CO2 in a 1:1 stoichiometric ratio under ideal conditions, with a large adsorption capacity. At the same time, low-temperature adsorption is suitable for CO2 sources with lower concentrations, with lower energy consumption and operating costs, and has broad room for future development. However, the current K2CO3-based adsorption materials still face the problems of poor cycle durability, difficulty in overall molding, and high difficulty in operation. Based on the above shortcomings, this invention uses commercial corrugated board blanks as carriers to synthesize modular K2CO3-based CO2 adsorption materials, which reduces the cost of adsorbent replacement and operation, and has good industrial application potential. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a CO2 adsorption material based on a corrugated board blank.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] The corrugated board blank is added into a modifier solution with a mass fraction of 2 to 10%, impregnated, dried, and then calcined;

[0009] Then, it is added into a K2CO3 solution with a mass fraction of 5 to 20%, reacted, and dried to obtain a CO2 adsorption material based on a corrugated sheet blank;

[0010] Wherein, the modifier includes one of urea or polyvinyl pyrrolidone.

[0011] As a preferred solution of the method for preparing the CO2 adsorption material based on the corrugated board blank of the present invention, the mass fraction of the modifier in the modifier solution is 5-10%, and the mass fraction of K2CO3 in the K2CO3 solution is 10-20%.

[0012] As a preferred embodiment of the method for preparing the CO2 adsorption material based on the corrugated board blank of the present invention, the impregnation time is 8 to 12 hours.

[0013] As a preferred scheme of the preparation method of CO2 adsorption material based on corrugated board blank described in the present invention, the ratio of the corrugated board blank to the modifier solution is 3-5g:5-6mL, and the ratio of the corrugated board blank to the K2CO3 solution is 3-5g:5-6mL.

[0014] As a preferred scheme of the preparation method of CO2 adsorption material based on corrugated board white embryo described in the present invention, when the modifier is urea, the calcination temperature is 240-260°C and the time is 2-4 hours; when the modifier is polyvinyl pyrrolidone, the calcination temperature is 430-460°C and the time is 2-4 hours.

[0015] As a preferred embodiment of the method for preparing the CO2 adsorption material based on the corrugated board blank of the present invention, the reaction time is 10 to 12 hours.

[0016] Another object of the present invention is to overcome the deficiencies in the prior art and provide a CO2 adsorption material based on corrugated board blanks prepared by the preparation method.

[0017] Another object of the present invention is to overcome the deficiencies in the prior art and provide the use of the CO2 adsorption material based on corrugated board blanks in flue gas CO2 adsorption.

[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for using a CO2 adsorbent material to adsorb CO2 in flue gas, which comprises: applying the CO2 adsorbent material based on corrugated sheet blank as claimed in claim 7, and further comprising:

[0019] The CO2 adsorption material based on corrugated plate blank is placed in the adsorption and desorption reaction tower of the fixed bed reactor. The flue gas composition includes 10-15% CO2, 5-10% H2O, 75-80% N2, and the flue gas flow rate is 0.5-1.0m 3 / h, the reaction temperature is 50-70℃, and the adsorption of CO2 in the flue gas is achieved.

[0020] As a preferred embodiment of the method for using the CO2 adsorbent material of the present invention to adsorb CO2 in flue gas, the CO2 capture capacity of the CO2 adsorbent material based on corrugated sheet is 1.0 to 1.9 mmol / g.

[0021] Beneficial effects of the present invention:

[0022] (1) The present invention utilizes commercial corrugated plate blanks to prepare CO2 adsorbent materials, which has the advantages of low cost and readily available raw materials, and can be prepared in a modular manner. The prepared CO2 adsorbent material based on corrugated plate blanks has a CO2 capture capacity of 1.0 to 1.9 mmol / g, has good CO2 adsorption performance, and has good industrial application potential.

[0023] (2) The present invention gives full play to the three-state pore characteristics of the corrugated sheet blank. The corrugated sheet blank has a high microscopic and macroscopic specific surface area, which provides favorable conditions for the loading of K2CO3. The carrier is further modified by urea or PVP pore-forming agent, which increases the loading sites of K2CO3, increases the adsorption active sites, and optimizes the adsorption effect.

[0024] (3) The CO2 adsorption material based on the corrugated plate blank of the present invention has an integral molding structure, is easy to assemble and scale up, has a large flow area, low bed resistance, and is easy to use for multiple load cycles during operation, which greatly reduces the operating cost of adsorbent replacement. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0026] Figure 1 This is a physical picture of the CO2 adsorption material based on the corrugated board blank in Example 1 of the present invention.

[0027] Figure 2 This is a diagram of the adsorption reaction bench for the CO2 capture performance test in Examples 1-6 of the present invention.

[0028] Figure 3This is a micropore / mesopore distribution diagram of the CO2 adsorption material based on the corrugated board blank in Examples 3 and 5 of the present invention and the carrier of the original corrugated board blank in Comparative Example 1.

[0029] Figure 4 This is a macropore distribution diagram of the CO2 adsorption material based on the corrugated board blank in Examples 3 and 5 of the present invention and the original corrugated board blank in Comparative Example 1. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0033] The main components of the corrugated board blank used in the present invention are glass fiber (SiO2), purchased from Beijing DeNOx; urea and K2CO3 are analytical grade, manufactured by Sinopharm, and polyvinyl pyrrolidone (PVP) MW8000-12000K15, manufactured by Adamas.

[0034] The method for determining the microscopic specific surface area of ​​the corrugated board blank in the present invention is as follows: 400 mg of the sample is taken, fully ground in a mortar, and then transferred to an adsorption tube, and the microscopic specific surface area is tested in an adsorption instrument (model: ASAP 2020PLUS).

[0035] The method for determining and calculating the potassium content of the adsorbent in the present invention is as follows: taking an adsorbent sample, pressing it into tablets, and then determining it by an X-ray fluorescence spectrometer.

[0036] The flue gas conditions and adsorption and desorption conditions for the CO2 capture performance test in the present invention are:

[0037] Flue gas composition: 10% CO2, 10% H2O, 80% N2, flue gas flow rate is 0.5m 3 / h, the adsorption temperature is 50-70℃, and the desorption temperature is 120-150℃.

[0038] The determination and calculation method of CO2 capture capacity in the present invention is shown in the following formula:

[0039]

[0040] In the formula, q a is the CO2 adsorption capacity of the adsorbent (mmolCO2 / g); Q is the mixed gas flow rate (L / min); ρ CO2 is the CO2 density (kg / cm 3 );m a is the mass of adsorbent (g); M CO2 is the molar mass of CO2 (g / mol); t is the adsorption time (s); C in is the initial content of CO2 (vol%); C out is the outlet content (vol%) after CO2 adsorption.

[0041] Example 1

[0042] This embodiment provides a method for preparing a CO2 adsorption material based on a corrugated board blank.

[0043] 300g of corrugated sheet blank was placed in 500mL of 2% urea solution, ultrasonically immersed for 8 hours, dried, and calcined at 240°C for 2 hours;

[0044] Then, the white blank was immersed in 500 mL of 10% K2CO3 solution, reacted for 10 hours, and finally dried to obtain a CO2 adsorption material based on the corrugated board white blank, which was recorded as sample 1.

[0045] Figure 1 This is a physical picture of the CO2 adsorption material based on corrugated board blank.

[0046] Example 2

[0047] The difference between this embodiment and embodiment 1 is that the mass fraction of urea in the urea solution is adjusted to 5%, and the mass fraction of K2CO3 in the solution is adjusted to 5%. Other operations are the same as those in embodiment 1. A CO2 adsorption material based on corrugated board blank is prepared, which is recorded as sample 2.

[0048] Example 3

[0049] The difference between this embodiment and embodiment 1 is that the mass fraction of urea in the urea solution is adjusted to 10%, and the mass fraction in the K2CO3 solution is adjusted to 20%. Other operations are the same as in embodiment 1. A CO2 adsorption material based on corrugated board blank is prepared, which is recorded as sample 3.

[0050] Example 4

[0051] This embodiment provides a method for preparing a CO2 adsorption material based on a corrugated board blank.

[0052] 300g of corrugated sheet blank was placed in 500mL of 2% PVP solution, ultrasonically immersed for 8 hours, dried, and calcined at 430°C for 2 hours;

[0053] Then, the white blank was immersed in 500 mL of 5% K2CO3 solution, reacted for 12 hours, and finally dried to obtain a CO2 adsorption material based on the corrugated board white blank, which was recorded as sample 4.

[0054] Example 5

[0055] The difference between this embodiment and embodiment 4 is that the mass fraction of PVP in the PVP solution is adjusted to 5%, and the mass fraction of K2CO3 in the solution is adjusted to 20%. The other operations are the same as those in embodiment 1. A CO2 adsorption material based on corrugated board blank is prepared, which is recorded as sample 5.

[0056] Example 6

[0057] The difference between this embodiment and embodiment 4 is that the mass fraction of PVP in the PVP solution is adjusted to 10%, and the mass fraction of K2CO3 in the solution is adjusted to 10%. Other operations are the same as those in embodiment 1. A CO2 adsorption material based on corrugated board blank is prepared, which is recorded as sample 6.

[0058] Comparative Example 1

[0059] This comparative example uses the original corrugated board blank as the adsorption material.

[0060] The microscopic specific surface area (BET) of the modified corrugated board blanks in Examples 1-6 and the original corrugated board blanks in Comparative Example 1 are shown in Table 1.

[0061] Table 1 Comparison of BET values ​​of different CO2 adsorption materials

[0062]

[0063]

[0064] It can be seen from Table 1 that with the increase of the pore-forming agent content, the BET value of the CO2 adsorption material shows an increasing trend, and the BET values ​​of samples 1-6 are significantly higher than those of the original corrugated board blank.

[0065] The K (potassium) content of different CO2 adsorbent materials is shown in Table 2.

[0066] Table 2 Comparison of K content of different CO2 adsorption materials

[0067] Adsorbent K content (%) Sample 1 28.2 Sample 2 22.1 Sample 3 34.6 Sample 4 25.3 Sample 5 36.6 Sample 6 30.8 Original corrugated board blank 0

[0068] It can be seen from Table 2 that after being impregnated with K2CO3 solutions of different concentrations, the K content in sample 5 is the highest, with a mass fraction of 36.6%.

[0069] The CO2 capture performance test was carried out on the six samples and the original corrugated board blank in comparative example 1. Figure 2 The diagram of the adsorption reaction bench for the CO2 capture performance test is shown in Table 3. The CO2 capture capacity of different adsorbents is shown in Table 3.

[0070] Table 3 Comparison of CO2 capture capacity of different CO2 adsorbent materials

[0071]

[0072]

[0073] It can be seen from Table 3 that the CO2 capture capacity of samples 1-6 is 1.0-1.9 mmol / g. When the modifier is urea, the CO2 capture capacity of sample 3 is the highest, and when the modifier is PVP, the CO2 capture capacity of sample 5 is the highest. Among all samples, sample 5 has the highest CO2 capture capacity, which is attributed to its highest BET and K loading. From the experimental data, it can be seen that the CO2 adsorption capacity is positively correlated with the specific surface area of ​​the carrier and the K loading, but when the K loading is further increased, the increase in adsorption capacity gradually tends to be flat.

[0074] The CO2 adsorption reaction mainly occurs on the surface of K2CO3, and the reaction rate is fast, which means that the specific surface area will directly affect the contact area between the reaction substrate and CO2, and then affect the capture capacity of the adsorption material. The high microscopic and macroscopic specific surface areas of the corrugated board provide favorable conditions for the loading of K2CO3. At the same time, the addition of pore-forming agents further increases the loading sites of K2CO3, increases the number of adsorption active sites, and optimizes the adsorption effect.

[0075] Figure 3 The micropore / mesopore distribution diagram of the carrier of the original corrugated board blank, sample 3, and sample 5. Figure 4 It is the macropore distribution diagram. It can be seen that the pore-forming agent mainly expands the mesopores of the corrugated board blank, and has little effect on the micropores and macropores.

[0076] Comparative Example 2

[0077] The difference between this comparative example and Example 1 is that conventional pore-forming agent polyvinyl alcohol (manufacturer: McLean Mw9000-10000, CAS No.: 9002-89-5) is used, and other parameters are the same as those in Example 1 to prepare the adsorbent.

[0078] Its CO2 capture capacity is 0.8mmol / g, which is much lower than sample 1 and other samples.

[0079] In summary, the present invention uses commercial corrugated sheet blanks to prepare CO2 adsorbent materials, which has the advantages of low cost and readily available raw materials, and can complete modular preparation. The prepared CO2 adsorbent material based on corrugated sheet blanks has a CO2 capture capacity of 1.0 to 1.9 mmol / g, has good CO2 adsorption performance, and has good industrial application potential. The present invention gives full play to the three-state pore characteristics of the corrugated sheet blanks. The corrugated sheet blanks have high microscopic and macroscopic specific surface areas, which provide favorable conditions for the loading of K2CO3; the carrier is further modified by urea or PVP pore-forming agents, which increases the loading sites of K2CO3, increases the adsorption active sites, and optimizes the adsorption effect. The CO2 adsorbent material based on corrugated sheet blanks has an integral molding structure, is easy to assemble, easy to scale up, has a large flow area, low bed resistance, and is easy to use for multiple load cycles during operation, which greatly reduces the cost of replacing the adsorbent.

[0080] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a CO2 adsorbent material based on a corrugated sheet blank, characterized in that: include, The corrugated board blank is added into a modifier solution with a mass fraction of 2 to 10%, impregnated, dried, and then calcined; Then, it is added into a K2CO3 solution with a mass fraction of 5 to 20%, reacted, and dried to obtain a CO2 adsorption material based on a corrugated sheet blank; Wherein, the modifier includes one of urea or polyvinyl pyrrolidone.

2. The method for preparing a CO2 adsorbent material based on a corrugated sheet blank according to claim 1, characterized in that: The mass fraction of the modifier in the modifier solution is 5-10%, and the mass fraction of K2CO3 in the K2CO3 solution is 10-20%.

3. The method for preparing a CO2 adsorbent material based on a corrugated sheet blank according to claim 1, characterized in that: The immersion time is 8 to 12 hours.

4. The method for preparing a CO2 adsorbent material based on a corrugated sheet blank according to claim 1, characterized in that: The ratio of the corrugated board white embryo to the modifier solution is 3-5 g: 5-6 mL, and the ratio of the corrugated board white embryo to the K2CO3 solution is 3-5 g: 5-6 mL.

5. The method for preparing a CO2 adsorbent material based on a corrugated sheet blank according to claim 1, characterized in that: When the modifier is urea, the calcination temperature is 240-260° C. and the time is 2-4 hours; when the modifier is polyvinyl pyrrolidone, the calcination temperature is 430-460° C. and the time is 2-4 hours.

6. The method for preparing a CO2 adsorbent material based on a corrugated sheet blank according to claim 1, characterized in that: The reaction time is 10 to 12 hours.

7. The CO2 adsorption material based on corrugated board blank prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the CO2 adsorption material based on corrugated board blank as claimed in claim 7 in CO2 adsorption in flue gas.

9. A method for using a CO2 adsorbent material to adsorb CO2 in flue gas, characterized in that: The method comprises applying the CO2 adsorption material based on the corrugated board blank as claimed in claim 7, and further comprising: The CO2 adsorption material based on corrugated plate blank is placed in the adsorption and desorption reaction tower of the fixed bed reactor. The flue gas composition includes 10-15% CO2, 5-10% H2O, 75-80% N2, and the flue gas flow rate is 0.5-1.0m 3 / h, the reaction temperature is 50-70℃, and the adsorption of CO2 in the flue gas is achieved.

10. The method for using the CO2 adsorbent material according to claim 9 to adsorb CO2 in flue gas, characterized in that: The CO2 capture capacity of the CO2 adsorbent material based on the corrugated board blank is 1.0 to 1.9 mmol / g.